Computational Analysis of 30 Kw Contra Rotor Wind Turbine. (16th August 2012) - Kumar, P. Santhana; Bensingh, R. Joseph; Abraham, A.
Abstract : The aim of this study is to optimize and analyze the characteristics of the upwind primary rotor and the downwind secondary rotor of the contra rotor wind turbine to increase the aerodynamic performance by using computational fluid dynamic (CFD). The main objective is to provide maximum energy that can be extracted by the primary and secondary rotor from the renewable resource of wind to increase the thrust power. For this purpose, two kinds of rotor configurations which are 3-bladed single and 3-bladed contra-rotating rotor were compared by using CFD. The results of the primary and secondary rotor are validated with measurements of the 30 KW Contra rotor wind turbine available on literature and plotted for power output. The optimum axial distance between the two rotors are investigated through CFD for increased performance. In addition, the increased thrust and torque for each rotor configuration are compared for aerodynamic feasibility.